2010
DOI: 10.1016/s0828-282x(10)70403-7
|View full text |Cite
|
Sign up to set email alerts
|

Intracavitary right coronary artery

Abstract: A 46-year-old physician with an intermediate pretest probability but strong family history of premature coronary artery disease was referred for cardiac computed tomography angiography. While the cardiac computed tomography angiography did not demonstrate significant atherosclerotic coronary artery disease, the right coronary artery (RCA) was noted to have an anomalous intracavitary course within the right atrium over a 2.5 cm segment (Figures 1 to 3). DiscussionThe presence of an intracavitary course of an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 3 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…Previous case reports of intra-atrial RCA evaluated by CT angiography have shown variable lengths of 2.5 to 5 cm. [ 2 3 ] After the intra- atrial course, the distal RCA emerged into the epicardium proximal to the crux. There was no evidence of narrowing either at the site of entry or at the exit of the RCA in the atrial wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous case reports of intra-atrial RCA evaluated by CT angiography have shown variable lengths of 2.5 to 5 cm. [ 2 3 ] After the intra- atrial course, the distal RCA emerged into the epicardium proximal to the crux. There was no evidence of narrowing either at the site of entry or at the exit of the RCA in the atrial wall.…”
Section: Discussionmentioning
confidence: 99%
“…Also, during coronary artery bypass surgery, inadvertent entry into the right atrium can lead to suction of air into the right atrium, causing an air lock of the cardiopulmonary bypass circuit. [ 2 3 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of anomalous course of the right coronary artery through the right atrium in population is approximately 0.09–0.1% [ 1 , 3 ]. Andrade et al emphasize its asymptomatic character and this is the reason why it is incidental finding [ 2 ]. The example of another anomaly is intracavitary course of proximal segment of left anterior descending artery in the right ventricle, which occurs in approximately 0.3% of the population [ 1 , 2 ].…”
Section: Descriptionmentioning
confidence: 99%
“…Anomalous course of the coronary artery may cause the risk of its injury during right heart catheterization, pacemaker implantation and ablation preceded by the electrophysiology testing [ 1 3 ]. An intracavitary right coronary artery could be disrupted, especially during ablation of typical atrial flutter which is performed along the cavotricuspid isthmus [ 1 , 2 ]. The disruption of left anterior descending artery going through the right ventricle is possible during ablation of right ventricular outflow tract [ 2 ].…”
Section: Descriptionmentioning
confidence: 99%
See 1 more Smart Citation